2002
DOI: 10.1002/eat.10042
|View full text |Cite
|
Sign up to set email alerts
|

Excessive exercise in anorexia nervosa and bulimia nervosa: Relation to eating characteristics and general psychopathology

Abstract: Possible explanatory models are advanced to account for this pattern of findings, focusing on the possible use of exercise as an affect regulation strategy among anorexia nervosa patients. Further research is suggested to test and develop this model, and possible clinical implications are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
155
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(187 citation statements)
references
References 13 publications
(11 reference statements)
23
155
1
8
Order By: Relevance
“…Changes in these variables were not significantly correlated in non-excessive exercisers. This supports previous suggestions of excessive PA as an affect regulation strategy, 7 and is consistent with the study of Long and Hollin 26 who found poor outcome of ED treatment associated with persistent negative addiction to exercise.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Changes in these variables were not significantly correlated in non-excessive exercisers. This supports previous suggestions of excessive PA as an affect regulation strategy, 7 and is consistent with the study of Long and Hollin 26 who found poor outcome of ED treatment associated with persistent negative addiction to exercise.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, and in accordance with previous studies, [5][6][7][8][9][10] excessive exercisers showed higher EDE and EDI scores, amount of PA, exercise dependence score, and importance of exercise as negative affect regulation compared to non-excessive exercisers. These findings support the seriousness of excessive PA behavior.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As pacientes com anorexia nervosa resistem em manter um peso mínimo para idade e estatura e insistem em ignorar os riscos de um peso muito baixo. Podem recorrer ao exercício físico excessivo para perder ainda mais peso 74 . Freqüentemente, em adolescentes e mulheres, o ciclo menstrual torna-se irregular, com amenorréias prolongadas.…”
Section: Transtornos Alimentares (Anorexia Nervosa E Bulimia Nervosa)unclassified
“…They may engage in excessive physical exercise to lose more weight. 74 Quite often, menstrual cycle becomes irregular in adolescents and women, with long periods of amenorrhea. Patients with bulimia nervosa have compulsion to eat excessively for short periods of time and, soon after that, they selfinduce vomiting, use laxatives, diuretics, enemas, or abuse of medications or physical exercise to prevent weight gain.…”
Section: Schizophreniamentioning
confidence: 99%